2014
DOI: 10.1007/s00253-014-6223-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering for improved production of ethanol by Corynebacterium glutamicum

Abstract: Recombinant Corynebacterium glutamicum harboring genes for pyruvate decarboxylase (pdc) and alcohol dehydrogenase (adhB) can produce ethanol under oxygen deprivation. We investigated the effects of elevating the expression levels of glycolytic genes, as well as pdc and adhB, on ethanol production. Overexpression of four glycolytic genes (pgi, pfkA, gapA, and pyk) in C. glutamicum significantly increased the rate of ethanol production. Overexpression of tpi, encoding triosephosphate isomerase, further enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Notably, in contrast to the ΔpfkB mutant that requires expensive fructose as a carbon source for cell growth to induce the enhanced productivity, the engineered strains that can use inexpensive glucose are cost-effective in commercial production. Although it has already been reported that overexpression of the glycolytic genes increases glucose consumption and productivity (11,15,49), we further demonstrate that overexpression of the PTS genes is also effective in C. glutamicum. These findings will be helpful in understanding the regulatory mechanisms of glycolytic flux and can be applicable to the improvement of microbial production of various kinds of useful chemicals.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Notably, in contrast to the ΔpfkB mutant that requires expensive fructose as a carbon source for cell growth to induce the enhanced productivity, the engineered strains that can use inexpensive glucose are cost-effective in commercial production. Although it has already been reported that overexpression of the glycolytic genes increases glucose consumption and productivity (11,15,49), we further demonstrate that overexpression of the PTS genes is also effective in C. glutamicum. These findings will be helpful in understanding the regulatory mechanisms of glycolytic flux and can be applicable to the improvement of microbial production of various kinds of useful chemicals.…”
Section: Resultsmentioning
confidence: 66%
“…Consequently, under anaerobic conditions, overexpression of GAPDH and perhaps of other glycolytic enzymes should be effective to enhance glycolytic flux. Indeed, we have demonstrated that glucose consumption and productivity were enhanced by overexpressing gapA (11), pyk, pfkA, pgi (49), and tpi (15) under oxygen deprivation, whereas gapA overexpression had no effect on the glucose consumption rate under aerobic conditions (11). In this study, overexpression of pgi, pfkA, tpi, gapA, and pgk increased oxygen-deprived glucose consumption and organic acid production as well (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…orynebacterium glutamicum represents one of the most important biotechnological platform organisms and massively contributes to the industrial production of amino acids (1)(2)(3)(4)(5), but it has also been engineered, for instance, for the production of lower alcohols (6)(7)(8)(9), organic acids (10-13), diamines (14,15), and carotenoids (16)(17)(18). However, currently applied expression setups show only moderate performance regarding both precise control and expression homogeneity.…”
mentioning
confidence: 99%
“…b Means and standard deviations of three replicates are given control by global regulators such as ArcA (Perrenoud and Sauer 2005). Overexpression of genes encoding glycolytic enzymes as applied in E. coli (Xie et al 2014;Seol et al 2015), B. subtilis ), or S. coelicolor (Borodina et al 2008) was also used for C. glutamicum, e.g., to improve the production of high value compounds like amino acids (Yamamoto et al 2012;Reddy and Wendisch 2014), alcohols (Jojima et al 2015;Yamamoto et al 2013), or the organic acid D-lactate (Tsuge et al 2015). Under these conditions or when a repressor gene of glycolysis genes was deleted, i.e., that of the DeoR-type transcriptional regulator SugR, high titers of L-lactate were formed as side effect of faster glucose utilization (Engels and Wendisch 2007;Engels et al 2008;Teramoto et al 2011).…”
Section: Discussionmentioning
confidence: 99%